(untitled) (Fiep Bulletin - online, 2011)
The study had for objective to correlate Functional Autonomy(FA), in aged hypertensive people, from the project "Caminha Juazeiro", registered in cadastre in two health center from Juazeiro do Norte – CE city. This research elapses of a descriptive, transversal study with 24 individuals (9 men; 15 women), of both genders, with average of age of (68,3+5,65) submitted to the protocol of evaluation of the FA of the group of Latin American development for the maturity, constituted by tests to walk 10 meters (W10M), to raise of the chair and to move themselves for the house (RCMH), to raise from sitting position (RSP) and to raise from the ventral decubitus position(RVDP).Descriptive statistics were used and pre - established point of cut; as inferencial test of correlation of "spearman" and test "t" of student for independent samples. The results found in the masculine group IG = (33,55+7,57); C10m = (8,02+2,40); LPS = (74+4,46); LCLC= (47,4+7,77); LPDV = (3,84+1,70) and feminine IG= (34,39+8,54); C10M= (7,54+1,62); LPS= (14,98+4,10); LCLC= (47,96+8,68); LPDV= (5,08+4,04). All the analyzed variables was in weak levels. The correlations showed itself strong between the variable age and C10M (r=0,894), gender and LCLC (r=0,977). The test of difference between averages disclosed not to have significant differences (p<0.05) in the variables analyzed in relation to gender. Concluding that both genders be revealed at the level of FA considered weak. This fact can generate significant negative impact on aspects related to health and quality of life, mainly because these individuals already have chronic degenerative diseases.